A FORMAÇÃO DOS CONCEITOS CIENTÍFICOS E O PROCESSO DE ENSINO-APRENDIZAGEM NOS ANOS INICIAIS DO ENSINO FUNDAMENTAL - Fernando Wolff Mendonça; Maria Eduarda dos Santos (Edufatecie, 2021)
This article aims to analyze the formation process of Scientific Concepts, according to the assumptions of Historical-Critical Pedagogy and Historical-Cultural Psychology, therefore, a theoretical deepening of the concepts of thought, language, psychological functions was sought. elementary, superiors and the mediation process. This study is classified as bibliographic and documentary. The following results were obtained through this research, the formation of concepts is a real and complex act ofthought that is influenced by the external means of cultural development (instruments and signs) and by the process of development of psychic functions. Conditions such as family experiences, the school environment and mediating teachers can influence thedevelopment of scientific concepts, there was also the importance of the union between language and thought for the formation of scientific concepts. We conclude that social interaction contributes to the process of forming scientific concepts and that the theoretical concepts present in the Historical-Cultural Theory are important for the development of contextualized and systematized pedagogical practices to students' learning objectives.